Madison's Metronome : The Constitution, Majority Rule, and the Tempo of American Politics. - Weiner, Greg. (La Vergne : University Press of Kansas, 2022)
Examines the significance of time in James Madison's theory of majority rule. Madison worried that the drive for instant political gratification might lead to an inflamed majority that would not rule reasonably. His philosophy-that the natural power of time will defuse passions-is incompatible with the current political ethos that values quick decision-making.
Cover -- Title Page -- Copyright Page -- Table of Contents -- Preface -- Introduction: ""The Sovereign Physician of our Passions -- 1. Madison on Majorities -- 2. Time and Tranquility -- 3. Time and the Tenth Federalist -- 4. Constitutional Metabolism -- 5. Politics and Patience -- Notes -- Bibliography -- Index -- Back Cover
Description based upon print version of record.
eBooks on EBSCOhost
Keywords: Madison, James, -- 1751-1836 -- Political and social views; Majorities; Republicanism -- United States -- History -- 18th century; Federal government -- United States -- History -- 18th century; United States -- Politics and government -- Philosophy; Majorité (Droit constitutionnel); Républicanisme -- États-Unis -- Histoire -- 18e siècle.; États-Unis -- Politique et gouvernement -- Philosophie; Revolutionary Period (1775-1800); United States; HISTORY; Political; PHILOSOPHY; Political Process; POLITICAL SCIENCE; Constitutions; Electronic books